Caribbean vision for social development : a collective position of Caribbean NGOs (The Project Port of SpainTT, 1995)
Defines the themes for the World Summit for Social Development. Explains the Caribbean vision for social development and discusses the processes by which it can be achieved at all levels.
Prepared for presentation and discussion at the Third Preparatory Committee...and the Social Summit, Copenhagen, March 1995.